A comparison of the prevalence and clustering of major cardiovascular risk factors in the Netherlands and China. (November 2016) - Wang, Xin; Bots, Michiel L; Yang, Fang; Sun, Jie; He, Shumei; Hoes, Arno W; Niu, Junqi; Vaartjes, Ilonca
Background: Cardiovascular risk factors tend to be clustered. Variations in clusters across populations have not been widely investigated. This study aims to compare the prevalence and clustering of major cardiovascular risk factors between adults in the Netherlands and China. Methods: A total of 6542 Dutch adults was recruited from 2001 to 2006 for the Utrecht Health Project, an ongoing cohort study among inhabitants of a newly developing area near Utrecht, the Netherlands. A total of 37, 141 Chinese employees who received health screening in Changchun City, China was enrolled from 2003 to 2010, and 3850 residents from Dehui, another city from northeast China, were enrolled in 2007. Results: The Dutch and Chinese populations shared similar patterns with increasing prevalence with age for most cardiovascular risk factors. Age-specific levels of body mass index, blood pressure and total cholesterol were higher in the Dutch than in the Chinese population. An exception to this was young men (18–44 years old): Chinese young men had similar body mass index levels compared to their Dutch counterparts. The age-standardised prevalence of current smoking was much higher in Chinese men compared to Dutch men ( P  < 0.05). The clustering patterns of risk factors differed between the Dutch and Chinese with the smoking-heavy drinking cluster while smoking-hypercholesterolemia was more common in both Dutch young men and women. Conclusions: Cardiovascular risk profiles and clustering patterns differ between the Dutch and the Chinese and seem to differ between men and women. This calls for race and sex-specific targeted prevention programmes.